Nightsong - Berk, Ari; Long, Loren (New York : Simon & Schuster Books for Young Readers, 2012)
Chiro, a young bat, is nervous about flying into the world for the first time without his mother, especially on a very dark night, but he soon learns to rely on his "song" to find his way and stay safe.
Keywords: Bats -- Fiction; Hearing in animals -- Fiction